ASPEK-ASPEK SOSIOLOGIS NOVEL LAMPAU KARYA SANDI FIRLY - Titik Wijanarti (Balai Bahasa Provinsi Papua, 2019)
The novel that raised or talked about the life of the Dayak’s people either as the background of the story or the main problem can be said is still a bit in the literary world of Indonesia. This study analyzed a novel which is based on the life of Dayak Meratus’s people of South Kalimantan titled Lampau by Sandi Firly. The focus of analysis in this research is the sociological aspects of the novel Lampau. In accordance with the problems and objectives of the study, the theoretical framework used in this research is the sociology of literature, especially sociology of literature that focuses on social issues in literary works. Based on the analysis of sociology of literature that has been done can be described four aspects of sociology in the novel that is the position and function of Balian in Meratus Dayak life, social gap of Meratus Dayak community, pesantren as an alternative social migration, and culture wander.